2001
DOI: 10.1136/heart.85.6.680
|View full text |Cite
|
Sign up to set email alerts
|

Equity in access to exercise tolerance testing, coronary angiography, and coronary artery bypass grafting by age, sex and clinical indications

Abstract: Objectives-To assess whether patients with heart disease in a single UK hospital have equitable access to exercise testing, coronary angiography, and coronary artery bypass graft surgery (CABG). Method-Retrospective analysis of patients' medical case notes (n = 1790), tracking each case back 12 months and forward 12 months from the patient's date of entry to the study. Setting-Single UK district hospital in the Thames Region. Patients-Patients (elective and emergency) with a cardiac ICD inpatient code at disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 36 publications
2
45
0
2
Order By: Relevance
“…Since the risk for elderly patients varies greatly, risk evaluations should be preferentially determined on an individual basis 19 . Studies using data banks confirmed the predominance of male patients 20,21 . Surgical indications for women are generally postponed due to conditions such as equivocal symptom interpretations and therefore a late diagnostic process.…”
Section: Discussionmentioning
confidence: 83%
“…Since the risk for elderly patients varies greatly, risk evaluations should be preferentially determined on an individual basis 19 . Studies using data banks confirmed the predominance of male patients 20,21 . Surgical indications for women are generally postponed due to conditions such as equivocal symptom interpretations and therefore a late diagnostic process.…”
Section: Discussionmentioning
confidence: 83%
“…This result suggests that in addition to the differences in the distribution of comorbid conditions, the relative risk associated with a comorbidity may help to explain the gender differences in the prognoses for MI and stroke. Moreover, considerably more men than women undergo invasive cardiac procedures and receive aggressive treatment (Bowling et al 2001;Shaw et al 2004;Blomkalns et al 2005;Smith et al 2009). The marked differences observed in the treatment strategies for men and women have been partially explained by differences in disease severity, comorbid conditions, symptom presentation, and patient preferences for surgical or less aggressive forms of treatment (Vaccarino et al 2003;Anand et al 2005).…”
Section: Sex Differences In Morbiditymentioning
confidence: 99%
“…Bond and colleagues previously examined the independent effects of both age and sex on the treatment of cardiac hospital patients in two district general hospitals. They reported that patients aged over 75 years, and women, independently, were significantly less likely to receive indicated interventions in one hospital; 1 and although significant age effects were found in the second hospital, there were fewer independent sex effects. 30 While the latter were all patients who had actually been referred (or admitted via emergency services) to specialist services, the reasons for the inequity experienced post-referral were unknown.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[1][2][3] Despite policies orientated specifically for the health and health care of older people emphasising equity, 4 age-related patterns of utilisation remain. 5 Coronary heart disease (CHD) is an important condition to consider; its risk increases with age, it remains the major cause of death in many countries, by 2020 it is predicted to be the leading cause of disease burden worldwide, 6 and, importantly, it has clear recommendations set out for appropriate treatment regimes.…”
Section: Introductionmentioning
confidence: 99%